Digital Empowerment:Improving Dasawisma's Capabilities in Online Marketing and Sales Through the Marketplace: Digital Empowerment: Peningkatan Kapabilitas Dasawisma Dalam Pemasaran Dan Penjualan Online Melalui Marketplace - Raafi’udin*, Ridwan; Rosmawarni, Neny; Dewi, Catur Nugrahaeni Puspita; Edyana, Fajar (Universitas Lancang Kuning, 2024)
This community service activity aims to improve the capabilities of dasawisma women in RW 10, Ciracas Village, Ciracas District, East Jakarta in digital marketing and online sales through the marketplace platform. Through a series of practical trainings, participants have been given an in-depth understanding of digital marketing concepts, effective online marketing strategies, and the use of various features in the marketplace platform. In addition, legal aspects, online security, and network development are also the focus, providing a strong foundation for participants to run an online business sustainably. With the aim of empowering the local economy, this activity is expected to help dasawisma women take advantage of the potential of the local economy and increase their contribution to local economic development, as well as this activity helps the government technically in relation to the community directly. This activity was attended by 120 participants and as many as 85 have provided feedback from the material and experience that has been given. The training material was delivered in lectures and discussions. For the lecture session, it was delivered by presenting material about digital marketing through the marketplace and comparing it in a conventional way. Broadly speaking, participants are able to accept and understand the use of digital marketing technology through the marketplace. Furthermore, the results of the implementation of community service activities were evaluated using a SWOT analysis with results showing a significant increase in understanding of online security and marketing. With the results of the training that show for the better, the community, especially dasawisma women, is ready to develop businesses both managed independently and business groups managed under the auspices of local residents.